2013
DOI: 10.5604/15093492.1058421
|View full text |Cite
|
Sign up to set email alerts
|

Subluxation of the shoulder joint in stroke patients and the influence of selected factors on the incidence of instability

Abstract: STRESZCZENIEWstęp. Ce lem ba dań by ła oce na czę sto ści wy stę po wa nia pod wich nię cia w sta wie ra mien nym u cho rych po przeby tym uda rze mó zgu oraz wpły wu re ha bi li ta cji i obec no ści lub bra ku pły nu w ka let kach pod bar ko wej i pod na ra miennej na wy stę po wa nie nie sta bil no ści.Materiał i metody. Gru pę ba da ną sta no wi ło 182 cho rych po prze by tym uda rze mó zgu. Wśród ba da nych było 108 mę żczyzn i 74 ko bie ty. U 156 cho rych udar miał cha rak ter nie do krwien ny, a u 26 ba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 10 publications
2
10
2
3
Order By: Relevance
“…Rajaratnam et al (2007) found that three simple bedside clinical tests (positive Neer test, pain during performance of the HBN manoeuver, and difference of greater than 10° of passive external rotation) provided a 98% probability of provisional diagnosis of HSP. These tests correspond with soft tissue abnormalities observed on ultrasonic examination of patients with HSP including effusion of subacromial–subdeltoid bursa and biceps tendon sheath and tenosynovitis/tendinopathy of supraspinatus, biceps, and subscapularis tendons (Lee et al, 2009; Pong et al, 2012; Pop, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…Rajaratnam et al (2007) found that three simple bedside clinical tests (positive Neer test, pain during performance of the HBN manoeuver, and difference of greater than 10° of passive external rotation) provided a 98% probability of provisional diagnosis of HSP. These tests correspond with soft tissue abnormalities observed on ultrasonic examination of patients with HSP including effusion of subacromial–subdeltoid bursa and biceps tendon sheath and tenosynovitis/tendinopathy of supraspinatus, biceps, and subscapularis tendons (Lee et al, 2009; Pong et al, 2012; Pop, 2013).…”
Section: Discussionsupporting
confidence: 66%
“…This is higher than the 25.3% and 37% reported by Pop (in Poland) (16) and Suethanapornkul et al . (17) (in Thailand), respectively, but lower than the 58% reported by Kumar et al .…”
Section: Discussioncontrasting
confidence: 63%
“…They found that ultrasonographic measurements of AGT distance have shown to be reliable and valid in the assessment of glenohumeral subluxation (GHS) in patients with stroke. Pop T 27 ) also found that there was no subluxation of the shoulder on the healthy side, while on the paretic side, subluxation occurred in 25.3% of the patients. Shoulder subluxation in lateral distances is a predictor for supraspinatus tendonitis 28 ) .…”
Section: Resultsmentioning
confidence: 90%